New Methods in Tornado Climatology. Issue 4 (April 2015) - Widen, Holly M.; Fricker, Tyler; Elsner, James B.
Abstract How climate change might affect tornadoes remains an open scientific question. Climatological studies are often contested due to inconsistencies in the available data. Statistical methods are used to overcome some of the data limitations. A few of these methods including using the proportion of tornadoes occurring on big tornado days, estimating tornado energy from the damage path, and modeling counts spatially are described here. The methods move beyond analyses of occurrences by damage ratings and spatial smoothing. Applications of these and related methods will help grow the nascent field of tornado climatology.